Penerapan Metode Linear Regression pada Analisis Komentar Negatif Konser Coldplay di Indonesia - Subiksa, Gde Brahupadhya; Ariawan, Made Pasek Agus; Peling, Ida Bagus Adisimakrisna (Yayasan Petra Harapan Bangsa, 2023)
Negative comments on international concert events can have a significant impact on the future conduct of such concerts. Possible impacts of negative comments include decreased interest from the audience, difficulty in gaining sponsorship and partner support, influence on decisions made by the artist or musical group, and safety considerations for the organizers, audience, and the artist or group. An analysis of negative comments on an international concert is necessary for an appropriate strategy to manage and mitigate negative impacts that may arise in the future. The benefits of analyzing the impact of negative comments on an international concert are diverse. The analysis can influence various aspects related to the implementation of the event and public perception. 72 negative comments have been classified using the linear regression method. Based on the results of the value of these negative comments, it can be stated that some of the words that trigger a comment to be considered as negative in the context of Coldplay concerts in Indonesia are words such as